2006
DOI: 10.1080/02652030500512037
|View full text |Cite
|
Sign up to set email alerts
|

Carry-over of dioxins and PCBs from feed and soil to eggs at low contamination levels – influence of mycotoxin binders on the carry-over from feed to eggs

Abstract: Laying hens were fed with compound feed containing six different levels of dioxins, dioxin-like PCBs and indicator PCBs for a period of 56 days. This was followed by a period of 56 days on clean feed. Dioxin levels in feed varied from background levels to three times the current EU tolerance limit of 0.75 ng TEQ/kg. At all dose levels a rapid increase was observed in the dioxin levels in eggs. There was a clear linear dose-response relationship between the dioxin levels in eggs and feed. The feed containing 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 15 publications
7
48
0
Order By: Relevance
“…In Table S1 results on bioaccumulation of individual dioxin congeners in eggs from hens reared outdoors are divergent. Some studies reported that the more highly chlorinated PCDD/F congeners bioaccumulated to the highest degree (Menotta et al, 2010;Hsu et al, 2010;Chang et al, 1989); however, these results conflict with findings from other studies, in which the accumulation of less chlorinated compounds was predominant De Pauw, 2005, 2006;Stephens et al, 1995;Schuler et al, 1997;Hoogenboom et al, 2006;Roszko et al, 2014;Rawn et al, 2012). Data presented in our study support this latter theory, highlighting the importance of fingerprinting PCDD/F sources to discover the origin of the contaminants.…”
Section: Predominance Of Dioxins and Pcb Congenerssupporting
confidence: 60%
“…In Table S1 results on bioaccumulation of individual dioxin congeners in eggs from hens reared outdoors are divergent. Some studies reported that the more highly chlorinated PCDD/F congeners bioaccumulated to the highest degree (Menotta et al, 2010;Hsu et al, 2010;Chang et al, 1989); however, these results conflict with findings from other studies, in which the accumulation of less chlorinated compounds was predominant De Pauw, 2005, 2006;Stephens et al, 1995;Schuler et al, 1997;Hoogenboom et al, 2006;Roszko et al, 2014;Rawn et al, 2012). Data presented in our study support this latter theory, highlighting the importance of fingerprinting PCDD/F sources to discover the origin of the contaminants.…”
Section: Predominance Of Dioxins and Pcb Congenerssupporting
confidence: 60%
“…Under steady state conditions, around 30% of the lower chlorinated compounds are transferred into milk, as compared to only 4% of the higher chlorinated congeners. Similar results were obtained in laying hens, showing carry-over rates of 53 and 59% for PCB 138 and 153, as compared to 49% for PCB 126 (Hoogenboom et al 2005). For both PCB as for PCDD/PCDF, the higher chlorinated compounds tend to accumulate in the liver.…”
Section: Behaviour Of Pcb and Pcdd/pcdf In Farm Animalssupporting
confidence: 74%
“…The first phase was followed by a much slower second phase, depending on the mobilization of PCB from the more poorly perfused fat tissues. Half-lives in laying hens for both PCB and PCDD/PCDF were determined to be around seven to eight weeks (Eijkeren et al, 2005). These half-lives are likely to vary with the breed and productivity of the animals.…”
Section: Behaviour Of Pcb and Pcdd/pcdf In Farm Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dioxin level in animal products (meat, eggs, and milk) is linked to the dioxin content in the feed by a linear relationship (Hoogenboom et al, 2006;Rideout and Teschke, 2004;Van Overmeire et al, 2009). While for animals reared indoor, the ingestion of dioxins is mainly linked to feedstuffs ingestion, animals reared outdoor ingest significant amounts of soil ranging from 0.5 to~8% of the dry weight ingested (Fries, 1996).…”
Section: Discussionmentioning
confidence: 99%